Quantification of the genetic change in the transition of Rhodnius pallescens Barber, 1932 (Hemiptera: Reduviidae) from field to laboratory (2009)
ABSTRACT: Previous studies have reported genetic differences between wild-caught sylvatic, domestic and laboratory populations of several Triatominae species. The differences between sylvatic and laboratory colonies parallel are similar to the differences observed between sylvatic and domestic populations. Laboratory colonies are frequently used as references for field populations, but the consequences of founder events on the genetic makeup of laboratory or domestic populations are rarely quantified. Our goal was to quantify the genetic change in Rhodnius pallescens populations artificially submitted to founder effects via laboratory colonization. We compared the genetic makeup of two sylvatic populations and their laboratory descendants using a panel of 10 microsatellite markers. Both sylvatic populations were initially collected from palm trees, but the colonies differed in the number of founder insects and amount of time kept in the laboratory. We evaluated allelic polymorphism, differences between expected and observed heterozygosity, estimates of population differentiation (Fst) and inbreeding (Fis, Fit) and cluster analyses based on Nei’s distances. We found a unique genetic structure for each sample population, with significant differentiation between the field insects and each of the laboratory generations. These analyses showed strong founder effects and showed that genetic drift had led to a genetic equilibrium over several generations of isolation. Our results suggest that laboratory colonies of R. pallescens have a different genetic structure than their wild relatives and similar processes likely affect other Triatominae laboratory stocks.